2017
DOI: 10.1007/s10549-017-4571-3
|View full text |Cite
|
Sign up to set email alerts
|

Adding high-intensity interval training to conventional training modalities: optimizing health-related outcomes during chemotherapy for breast cancer: the OptiTrain randomized controlled trial

Abstract: PurposeExercise training is an effective and safe way to counteract cancer-related fatigue (CRF) and to improve health-related quality of life (HRQoL). High-intensity interval training has proven beneficial for the health of clinical populations. The aim of this randomized controlled trial was to compare the effects of resistance and high-intensity interval training (RT–HIIT), and moderate-intensity aerobic and high-intensity interval training (AT–HIIT) to usual care (UC) in women with breast cancer undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
230
4
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(254 citation statements)
references
References 52 publications
8
230
4
12
Order By: Relevance
“…A recent review of Powers et al (2019), including preclinical studies, suggests that endurance exercise training performed prior to doxorubicin treatment protects against doxorubicin‐induced skeletal muscle atrophy by the prevention of excess oxidative stress and the activation of proteolytic signalling pathways . Indeed, the beneficial effects of exercise are confirmed in human studies with several clinical trials showing that combined resistance and endurance training has positive effects on muscle strength in cancer patients undergoing chemotherapy . Mijwel et al (2018) compared the effects of different exercise regimens (moderate‐intensity aerobic combined with high‐intensity interval training vs resistance combined with high‐intensity interval training) with usual care on skeletal muscle morphology in breast cancer patients receiving chemotherapy and found that resistance combined with high‐intensity interval training resulted in a significant increase in type I muscle fibres, whereas aerobic combined with high‐intensity training counteracted a decline in type I muscle fibres .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of Powers et al (2019), including preclinical studies, suggests that endurance exercise training performed prior to doxorubicin treatment protects against doxorubicin‐induced skeletal muscle atrophy by the prevention of excess oxidative stress and the activation of proteolytic signalling pathways . Indeed, the beneficial effects of exercise are confirmed in human studies with several clinical trials showing that combined resistance and endurance training has positive effects on muscle strength in cancer patients undergoing chemotherapy . Mijwel et al (2018) compared the effects of different exercise regimens (moderate‐intensity aerobic combined with high‐intensity interval training vs resistance combined with high‐intensity interval training) with usual care on skeletal muscle morphology in breast cancer patients receiving chemotherapy and found that resistance combined with high‐intensity interval training resulted in a significant increase in type I muscle fibres, whereas aerobic combined with high‐intensity training counteracted a decline in type I muscle fibres .…”
Section: Discussionmentioning
confidence: 99%
“…b Participants who did not drop out before baseline (n = 210) UC overall n = 60, weak-normal SOC n = 42, strong SOC n = 18. b Total effects of the exercise interventions on fatigue, symptoms, and health-related quality of life have been previously reported [12] population, the distribution includes a larger proportion of people with strong SOC (33% vs. 39% individuals with strong SOC, respectively) [30]. It has been shown that SOC is positively associated with perceived health [11].…”
Section: Sense Of Coherencementioning
confidence: 95%
“…In total, 240 women signed informed consent and 182 (76%) participants completed both baseline and follow-up testing (Appendix 1) [12]. Two hundred and forty women with breast cancer undergoing chemotherapy were randomly allocated to either AT-HIIT (n = 80), RT-HIIT (n = 79), or UC (n = 81).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer-related fatigue was selfassessed at baseline and at 16 wk using the EORTC QLQ-C30 questionnaire (version 3.0) (31). Muscle strength and EORTC-QLQ-C30 questionnaire results including all patients of the OptiTrain trial have been published previously (32). Higher scores on the EORTC-QLQ-C30 scale indicate higher levels of fatigue.…”
Section: Other Measuresmentioning
confidence: 99%